People interact closer when a face mask is worn but risk compensation is at best partial. - Aranguren, Martin; Cartaud, Alice; Cissé, Ibrahima; Coello, Yann (European Journal of Public Health, 2023)
Background Wearing a face mask and keeping a minimal distance from others are common nonpharmaceutical interventions that governments may mandate or recommend to contain the spread of infectious diseases. The article addresses the following questions: (i) Do people interact closer when the face mask is worn? (ii) Do people interact closer because they believe that the mask reduces the risk of contagion? (iii) If the mask induces people to interact closer, does the increase in risk entailed by shorter distances entirely offset the decrease in risk offered by the mask? Methods With a view to maximizing both the external and the internal validity of the study, between 2021 and 2022 we performed a large field experiment on real-life interactions (n  > 4500) and a controlled laboratory experiment in virtual reality. Results Converging between the field and the lab, the results indicate that in general people interact closer when the mask is worn, and in particular when they believe that the mask reduces the risk of contagion. However, even assuming a very low filtration efficacy and an extremely large distance-reducing effect of the mask, the counteracting effect of shorter interpersonal distances is never strong enough to entirely offset the mask's protection. Conclusion The distance-reducing effect of the mask is real but warrants no serious objection against a face mask policy.